HLA class II “typing”: Direct sequencing of DRB, DQB, and DQA genes - Santamaria, Pere; Boyce-Jacino, Michael T.; Lindstrom, Alan L.; Barbosa, Jose J.; Faras, Anthony J.; Rich, Stephen S. (Human immunology, 1992)
Routine clinical HLA class II typing is based largely on serological and cellular methods. These methods have many drawbacks that have led to the evaluation of molecular approaches to typing, including restriction fragment length polymorphism studies and oligotyping. We present here an alternative molecular approach, sequence-based typing (SBT), that allows direct determination of the sequences of all HLA class II polymorphic genes, thus providing the most detailed information currently possible in this regard. The data presented here using SBT are based on direct sequencing of polymerase chain reaction (PRC)-amplified DRB, DQB, and DQA cDNAs using a limited number of oligonucleotides. The oligonucleotides are designed to allow simultaneous determination of allelic sequences in any hetrozygote as well as characterization of DRB isotypic complexity. Two types of amplification oligonucleotides (nonconserved and/or conserved) are used for DRB typing, which involves a maximum of four simultaneous cDNA/PCR/sequencing reactions. The first of these reactions only uses conserved oligonucleotides and is designed to detect all the different DRB transcripts present in any given heterozygote; the other three reactions use nonconserved oligonucleotides and are designed to ensure the unambiguous interpretation of the most complex DRB heterozygote combinations. Characterization of DQA1 and DQB1 sequences can be performed by using conserved oligonucleotides and only involves one reaction per locus. We have applied SBT to 43 homozygous cell lines and to 38 different heterozygote combinations that had previously been serologically typed. In all cases we were able to determine the allelic composition at DRB1, DRB3/4/5 and/or DQB1, and DQA1 loci of these cell lines and subjects; our results, analyzed by blind protocol, were consistent with the serological phenotypes. SBT can be extended to class I and class III genes and is automatable. We believe that this strategy deserves further evaluation as a possible HLA typing method. Human Immunology 33, 69–81 (1992)